About Natural Scientific Views Of The Universe - Berdiyev U.B. (Genius Journals, 2023)
The article interprets the scientific view of the universe, based on the natural sciences. Some concepts of the scientific picture of the Universe include the achievements of science that determine man's place in it. In this case, the scientific picture is not a sum of general knowledge, but an integral system of ideas about the general properties, state and laws of nature
Keywords: Newton; classical mechanics; thermodynamics